Primitive neuroectodermal tumour of the kidney presenting as diplopia secondary to skull metastasis. Issue 12 (29th December 2019) - Rajaian, Shanmugasundaram; Pragatheeswarane, Murugavaithianathan; Krishnamurthy, Karrthik; Chakravarthy Narasimhachar, Srinivas
Abstract : A 20-year-old man presented to the department of neurology with diplopia, occipital headache and right flank pain for 1-week duration. CT of the brain revealed skull metastasis with heterogeneously enhancing dural-based mass lesion at the occipital region. Positron emission tomography revealed tracer avid soft tissue mass involving the upper pole of the right kidney with loss of fat planes with the inferior surface of the liver. Multidisciplinary team approach was discussed. He underwent palliative nephrectomy with lymph nodal mass excision. Biopsy from the renal mass was suggestive of primitive neuroectodermal tumour. He developed progressive liver metastases in spite of adjuvant chemotherapy denoting very aggressive disease.